2013
DOI: 10.1177/1470320312471229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II type 1 receptor blocker on bones in mice with type 1 diabetes induced by streptozotocin

Abstract: Local bone RAS functionally played a role in the development of type 1 diabetic osteoporosis, and losartan had no bone-sparing function in diabetes mice because of enhance skeletal RAS activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…Blockade of the RAS with ACEI and ARB inevitably disrupts the negative feedback loop that is critical for maintaining renin homeostasis, leading to compensatory induction of renin [5,41]. This is the main cause accounting for that the treatment with losartan (belongs to ARB) alone could not exert beneficial effects on diabetes-induced osteoporosis [42] and hyperglycemia-induced renal disease [5] in type 1 diabetic mice. The emerging clinical evidences Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Blockade of the RAS with ACEI and ARB inevitably disrupts the negative feedback loop that is critical for maintaining renin homeostasis, leading to compensatory induction of renin [5,41]. This is the main cause accounting for that the treatment with losartan (belongs to ARB) alone could not exert beneficial effects on diabetes-induced osteoporosis [42] and hyperglycemia-induced renal disease [5] in type 1 diabetic mice. The emerging clinical evidences Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Agtr1a loss-of-function protects against bone loss in both age-related and ovariectomy (OVX)-induced osteoporosis mouse models [28]. Among all of the various in vivo studies on AngII signaling in bone, the protection against OVX-induced bone loss has been the most reproducible in mice [29] and has also been recapitulated in rat models [10,30]. Collective studies emphasize beneficial role to bone health by inactivating Agtr1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…ANG II, active peptide within RAS, plays a pathological role in development of osteopenia and osteoporosis through activating osteoclastogenesis and inhibiting osteogenesis by binding to Type 1 receptor (AT1R; Nakai et al, ; Shimizu et al, ). In vivo and in vitro studies showed that the increased activity of skeletal RAS, especially the overactivation of the renin/renin receptor axis and the ACE/ANG II/AT1R signaling, was detrimental to bone tissue during hyperglycemia (Li et al, ; Yamamoto et al, ; Zhang et al, ; Zhang et al, ). Therefore, the RAS inhibitors, including renin inhibitor, ACE inhibitor (ACEI), and ANG II receptor blocker (ARB), exerted beneficial effects on skeletal system in animal studies (Zhang, Wang, Song, et al, ) and clinical studies (Yamamoto et al, ), even though these drugs in clinic are mainly prescribed for treating hypertension.…”
Section: Introductionmentioning
confidence: 99%